Endothelial cell‐derived endothelin‐1 is involved in abnormal scar formation by dermal fibroblasts through RhoA/Rho‐kinase pathway. Issue 8 (10th March 2017) - Kiya, Koichiro; Kubo, Tateki; Kawai, Kenichiro; Matsuzaki, Shinsuke; Maeda, Daisuke; Fujiwara, Toshihiro; Nishibayashi, Akimitsu; Kanazawa, Shigeyuki; Yano, Kenji; Amano, Genki; Katayama, Taiichi; Hosokawa, Ko
Abstract: Hypertrophic scars and keloids are characterized by excessive dermal deposition of extracellular matrix due to fibroblast‐to‐myofibroblast differentiation. Endothelin‐1 (ET‐1) is primarily produced by vascular endothelial cells and plays multiple roles in the wound‐healing response and organ fibrogenesis. In this study, we investigated the pathophysiological significance of ET‐1 and involvement of RhoA, a member of the Rho GTPases, in hypertrophic scar/keloid formation. We found that ET‐1 expression on dermal microvascular endothelial cells (ECs) in hypertrophic scars and keloids was higher than that in normal skin and mature scars. We also confirmed that ET‐1 induced myofibroblast differentiation and collagen synthesis in cultured human dermal fibroblasts through the RhoA/Rho‐kinase pathway. Finally, since hypertrophic scar/keloid formation was most prominent in areas exposed to mechanical stretch, we examined how mechanical stretch affected ET‐1 secretion in human dermal microvascular ECs, and found that mechanical stretch increased ET‐1 gene expression and secretion from ECs. Taken together, these results suggest that dermal microvascular ECs release ET‐1 in response to mechanical stretch, and thereby contribute to the formation of hypertrophic scars and keloids through the RhoA/Rho‐kinase pathway.